2020
DOI: 10.31235/osf.io/e6msz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

U.S. Regional Disparities in Physical Distancing: Evaluating Racial and Socioeconomic Divides During the COVID-19 Pandemic

Abstract: ObjectiveTo examine regional variation in physical distancing trends over the course of the COVID-19 pandemic, and to investigate inequalities within regions by race and socioeconomic status (SES).MethodsRace and SES information from the American Community Survey were matched with location data from mobile device location pings at the Census block group level. We present trends in the proportion of residents staying at home by Census region, race, and SES from February-August, 2020.ResultsFrom March-August, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Finally, consistent with Zang's report [49] who showed that of the four Census regions, Southerners had the lowest physical distancing rates, we found that respondents residing in areas of the country other than the South had better odds of Perfect Adherence than those in the South.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, consistent with Zang's report [49] who showed that of the four Census regions, Southerners had the lowest physical distancing rates, we found that respondents residing in areas of the country other than the South had better odds of Perfect Adherence than those in the South.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the opposite pattern might be expected. Lower-SES parents and Black and Latinx parents disproportionately occupied frontline positions and thus were less likely to work remotely while caring for their children at home (Blau et al, 2021;Lyttelton et al, 2020;Zang et al, 2020). Further, qualitative research demonstrated that "gendered caregiving norms … limited mothers' sense of entitlement to support from nonparental caregivers even if outside caregivers were available to help," often prompting parents who worked remotely to try getting by with little or no nonparental support (Calarco, Meanwell, et al, 2021, p. 8).…”
Section: Childcare During the Covid-19 Pandemicmentioning
confidence: 99%
“…Consider for instance these three observations: 1. Physical distancing guidelines are not uniformly followed, whether as a function of socioeconomic status (Weill et al, 2020) or geographic location (Zang et al, 2020; see also Kashima et al, 2021, for further discussion of cultural differences in the handling of COVID-19). 2.…”
Section: The Public Good Is Under Attackmentioning
confidence: 99%